2011
DOI: 10.1128/jb.00980-10
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Interactions between Germinants and Clostridium difficile Spores

Abstract: Germination of Clostridium difficile spores is the first required step in establishing C. difficile-associated disease (CDAD). Taurocholate (a bile salt) and glycine (an amino acid) have been shown to be important germinants of C. difficile spores. In the present study, we tested a series of glycine and taurocholate analogs for the ability to induce or inhibit C. difficile spore germination. Testing of glycine analogs revealed that both the carboxy and amino groups are important epitopes for recognition and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(157 citation statements)
references
References 39 publications
(56 reference statements)
9
142
5
1
Order By: Relevance
“…Position 17 of the D ring seems to be especially sensitive to deactivation by the presence of a hydroxyl group. This pattern of progesterone analog recognition contrasts with the recognition of bile salts by C. difficile spores, where both germinants and inhibitors require hydroxyl groups at least at positions 3, 7, and/or 12 (24).…”
Section: Discussionmentioning
confidence: 79%
“…Position 17 of the D ring seems to be especially sensitive to deactivation by the presence of a hydroxyl group. This pattern of progesterone analog recognition contrasts with the recognition of bile salts by C. difficile spores, where both germinants and inhibitors require hydroxyl groups at least at positions 3, 7, and/or 12 (24).…”
Section: Discussionmentioning
confidence: 79%
“…Histologically, the rifalazil treated animals had less edema and neutrophil infiltration than the vancomycin treated animals. When vancomycin was discontinued, 65% of the animals developed disease, while none of the rifalazil treated animals had positive toxin assays or disease [202] . Future trials of rifalazil in humans with CDI are eagerly anticipated, especially given the low relapse rate in animal models.…”
Section: Rifalazilmentioning
confidence: 99%
“…Since only the vegetative form produces toxin, theoretically prevention of spore germination would prevent symptomatic infection. Howerton et al [202] demonstrated that a cholate meta-benzene sulfonic derivative (CamSA) is a strong competitive inhibitor of taurocholate-mediated C. difficile spore germination. Subsequently, they administered a single 50 mg/kg dose of CamSA to mice infected with C. difficile spores and were able to prevent any signs of CDI [203] .…”
Section: Probioticsmentioning
confidence: 99%
“…When ingested, the multiple layers of the spore help protect it from stomach acids and digestive enzymes. Spore germination occurs upon interaction with the appropriate germinants within the intestinal tract, which include taurocholic acid, a taurineconjugated bile acid, and glycine [47,48] . The receptor for taurocholic acid on a C. difficile spore, CspC, was only recently discovered [49] , and researchers demonstrated that mutations to this protein …”
Section: Difficile Pathogenesis and Lifecyclementioning
confidence: 99%
“…This complex process has not been well studied in C. difficile but has in related species [51] . Germination normally occurs within the cecum and colon as other factors in the small intestine, such as high concentration of chenodeoxycholic acid, act to suppress widescale germination [48] . Subsequently, C. difficile initiates the activation of the pathogenicity locus (PaLoc) in the genome.…”
Section: Epidemiology and Risk Factors For CDImentioning
confidence: 99%